The Synthesis of Pyrido-fused 8-Methoxy Carbazoles by Using a Light-Assisted, Base Mediated Cyclization Reaction - Magagula, Bongi Florence (University of the Witwatersrand, Johannesburg, 2023)
Nitrogen-containing compounds such as indoles and carbazoles are significant classes of the N-heterocycles that show great promise as anti-cancer compounds. Indoles such as 2,3-diarylindole, 3-pyranyl indole and carbazoles such as 9-methoxyellipticine are compounds which possess anticancer or antitumor properties. Due to the favourable biological activities of N-heterocyclic compounds, medicinal and synthetic chemists have developed numerous methodologies for their synthesis. In this research project, the broad aim was to synthesize pyrido-fused carbazoles from 5-methoxyindole using methodologies that have been previously used in our laboratories and by other chemists while changing the position of the nitrogen atom on the pyrido-fused carbazoles. The first step in the synthesis of these carbazoles was the treatment of 5-methoxyindole with di-tert-butyl dicarbonate in the presence of 4-dimethylaminopyridine (DMAP) which gave the desired protected indole, tert-butyl 5-methoxy-1H-indole-1-carboxylate in excellent yields (90-99%). Exposure of the tert-butyl 5-methoxy-1H-indole-1-carboxylate to lithium 2,2,6,6-tetramethypiperidide followed by quenching with triisopropyl borate and hydrochloric acid gave (1-(tert-butoxycarbonyl)-5-ethoxy-1H-indol-2-yl)boronic acid. Using this and various halogen substituted pyridines, for example 3-bromo-4-methylpyridine in the Suzuki-Miyaura coupling reaction gave tert-butyl 5-ethoxy-2-(4methylpyridin-3-yl)-1H-indole-1-carboxylate (83% yield). This was further reacted with paraformaldehyde and iron (III) chloride or phosphorus oxychloride and DMF. After the removal of tert-butoxycarbonyl protecting group utilizing various methods this produced 5-methoxy-2-(4-methylpyridin-3-yl)-1H-indole-3-carbaldehyde (48% yield). 5-Methoxy-2-(4-methylpyridin-3-yl)-1H-indole-3-carbaldehyde possesses all the carbons of the final compounds and is suitably functionalized to partake in the key photo-induced and ase-mediated cyclization reaction. Previous studies pointed to the necessity of an alkyl protecting group on the indole-N atom. As a result, the indole nitrogen atom was then protected again with a methyl or a benzyl group; where the N-benzyl could be removed at a later stage. For example, reaction of 5-methoxy-2-(4-methylpyridin-3-yl)-1H-indole-3-carbaldehyde dissolved in THF, potassium hexamethyldisilazide and benzyl bromide furnished 1-benzyl-5-methoxy-2-(4-methylpyridin-3-yl)-1H-indole-3-carbaldehyde (83% yield). The key step in this synthesis was the light-assisted, base-mediated cyclization reaction which has been reported by de Koning and co-workers, where a solution of 1-benzyl-5-methoxy-2-(4-methylpyridin-3-yl)-1H-indole-3-carbaldehyde dissolved in dry DMF and potassium tert-butoxide was heated and irradiated with medium mercury lamp yielding the desired pyrido fused carbazole, 11-benzyl-8-methoxy-11H-pyrido[3,4-a]carbazole in a good yield of 70%. Following the outlined synthetic procedure depicted above, we were able to synthesize 5 analogues of 11-benzyl-8-methoxy-1H-pyrido[3,4-a]carbazole.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science, to the Faculty of Science, School of Chemistry, University of the Witwatersrand, Johannesburg, 2023.
Keywords: N-heterocyles; Carbazoles; Anti-cancer; Cyclization reaction; UCTD; SDG-3: Good health and well-being